AN ASSESSMENT ON THE INFLUENCE OF MANAGEMENT COMMUNICATION PRACTICES ON STUDENTS’ UNREST IN PUBLIC SECONDARY SCHOOLS IN MERU COUNTY, KENYA - Marete, Jacob Bundi; Mugwe, Dr. Mary; Reche, Prof. George N. (IJRDO- Journal of Educational Research, 2017)
The purpose of this research was to investigate the school management practices on communication factors contributing to student unrest in public secondary schools in Meru County, Kenya. The objectives focused on critical challenges facing principals and teachers in communicating effectively within the school. The research was carried out using the mixed method of research study in which the target population was 1,900 Principals, 1,900 Guidance and Counselling Masters/Mistresses, 1,900 Discipline Masters, 1,900 student Presidents, 19,200 students and 1 County Education Officer. The results showed that although the basic communication model of sender- message-receiver is straight forward, though communication barriers popularly referred to as “noise”. Noise in a school may be related to poor listening skills, poor language skills, a lack of trust and lack of follow-up/feedback on issues concerning students. Others include technical problems, poor selection of medium and misrepresentation of the message which may occur in the communication process.